Bronchiolitis Admissions in a Lebanese Tertiary Medical Center: A 10 Years' Experience - Naja, Zeina; Fayad, Danielle; Khafaja, Sarah; Chamseddine, Sarah; Dbaibo, Ghassan; Hanna-Wakim, Rima (Frontiers in Pediatrics, 2019)
Bronchiolitis and more specifically respiratory syncytial virus (RSV) bronchiolitis is a leading cause of global childhood morbidity and mortality. Despite the previous identification of possible risk factors associated with the severity of bronchiolitis, the data from Lebanon remains limited. We described the burden of bronchiolitis hospitalizations in children under 5 years of age in a tertiary care center in Lebanon from October 2004 to October 2014 and identified the risk factors associated with severe bronchiolitis. This was a retrospective cohort study conducted at the American University of Beirut Medical Center. Records of children younger than 5 years of age admitted with a diagnosis of bronchiolitis were reviewed. More than half the patients were RSV positive. RSV bronchiolitis was found to be significantly associated with longer hospital stay compared to children with non-RSV bronchiolitis (P = 0.007). Children exposed to smoking had an increased risk for longer hospital stay (P = 0.002) and were more likely to require ICU admission (P < 0.001) and supplemental oxygen (P = 0.045). Congenital heart disease was found to be a significant risk factor for severe bronchiolitis (P < 0.005). Conclusion: Patients with RSV bronchiolitis had a longer hospital stay compared to patients with non-RSV bronchiolitis. Exposure to smoking was associated with a more severe and complicated RSV infection. Congenital heart disease was the only risk factor significantly associated with all markers of bronchiolitis disease severity.